The Main Trends in the International Effort to Strengthen Global Liquidity after the Financial Crisis of 2008/2009 - Petr Sedláček (Czech Journal of International Relations, 2011)
Significant international attention has been directed to the most pressing problem of the financial crisis of 2008/2009 – global liquidity shortages. The use of adequate foreign exchange reserves during the crisis helped alleviate pressures. However, this was only partially effective in a number of important cases. Some countries also needed to rely on external official financing. The aim of this article is to compare and analyse the main sources of official global liquidity - foreign exchange reserves, bilateral swap lines of central banks, regional financial arrangements and IMF resources. To reach effective outcomes in relation to the accumulation of FX reserves and a strengthening of the global financial safety nets, effective international coordination will be necessary.